2014
DOI: 10.1128/jvi.03553-13
|View full text |Cite
|
Sign up to set email alerts
|

Limited Hepatitis B Virus Replication Space in the Chronically Hepatitis C Virus-Infected Liver

Abstract: We compared the kinetics and magnitude of hepatitis B virus (HBV) infection in hepatitis C virus (HCV)-naive and chronically HCV-infected chimpanzees in whose livers type I interferon-stimulated gene (ISG) expression is strongly induced. HBV infection was delayed and attenuated in the HCV-infected animals, and the number of HBV-infected hepatocytes was drastically reduced. These results suggest that establishment of HBV infection and its replication space is limited by the antiviral effects of type I interfero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
22
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 30 publications
3
22
0
Order By: Relevance
“…Our observation that innate immune activation restricts HBV infection is consistent with studies showing that HBV can be cleared from the liver in a cytokine-mediated, noncytotoxic manner (25,32), and that HBV replication is significantly reduced in chimpanzees chronically infected with HCV because of the induction of the type I IFN response (33). In contrast to the robust induction of ISGs in HBV-infected MPCCs, and to a lesser extent in iHeps, no ISG response was observed in HBV-permissive HepG2 cells overexpressing NTCP.…”
Section: Discussionsupporting
confidence: 78%
“…Our observation that innate immune activation restricts HBV infection is consistent with studies showing that HBV can be cleared from the liver in a cytokine-mediated, noncytotoxic manner (25,32), and that HBV replication is significantly reduced in chimpanzees chronically infected with HCV because of the induction of the type I IFN response (33). In contrast to the robust induction of ISGs in HBV-infected MPCCs, and to a lesser extent in iHeps, no ISG response was observed in HBV-permissive HepG2 cells overexpressing NTCP.…”
Section: Discussionsupporting
confidence: 78%
“…If and how HBV is detected by the innate immune system has remained an important yet unresolved issue. In contrast to many other viruses, HBV is generally thought to be a "stealth" virus because it does not induce a type I IFN response during natural or experimental infections (19)(20)(21)(22)(23)(24). This is thought to be related to the unique replication cycle of the virus.…”
mentioning
confidence: 99%
“…This adaptive response is able to clear the virus in the vast majority (90 to 95%) of immunocompetent adults (29). In addition to cytotoxic effector lymphocytes that directly kill infected cells, soluble immune effectors (such as type I and type III IFN, tumor necrosis factor alpha [TNF-␣], and interleukin 6 [IL-6]) elicit strong, noncytolytic antiviral effects targeting multiple stages of the HBV replication cycle, including transcriptional and posttranscriptional suppression of viral RNA expression, blocking of NC assembly, and destabilization of preformed NCs (24,25,(30)(31)(32)(33)(34)(35)(36)(37). Intriguingly, as demonstrated in an HBV transgenic-mouse model, IFN can also stimulate, rather than suppress, HBV gene expression and replication when viral replication levels are low (38), suggesting that HBV may have evolved to coopt the host antiviral response to enhance its own replication.…”
mentioning
confidence: 99%
“…Surprisingly, however, intrahepatic gene expression profiling in acutely HBV-infected chimpanzees revealed that HBV does not induce detectable ISGs or other cellular gene expression as it spreads throughout the liver (Fig. 1A) (Wieland et al 2004a(Wieland et al , 2014Wieland and Chisari 2005). This observation indicated that, unlike HCV, HBV acts like a "stealth virus," which is invisible to the innate immune system (Wieland et al 2004a;Wieland and Chisari 2005).…”
Section: Absence Of An Innate Response By Hbv-infected Cellsmentioning
confidence: 96%